Improvement of photosynthesis in rice (Oryza sativa L.) by inserting the C4 pathway - Karki, Shanta; Rizal, Govinda; Quick, William Paul (Springer, 2013)
To boost food production for a rapidly growing global population, crop yields must significantly increase. One of the avenues being recently explored is the improvement of photosynthetic capacity by installing the C4 photosynthetic pathway into C3 crops like rice to drastically increase their yield. Crops with an enhanced photosynthetic mechanism would better utilize the solar radiation that can be translated into yield. This subsequently will help in producing more grain yield, reduce water loss and increase nitrogen use efficiency especially in hot and dry environments. This review provides a summary of the factors that need to be modified in rice so that the C4 pathway can be introduced successfully. It also discusses the differences between the C3 and C4 photosynthetic pathways in terms of anatomy, biochemistry and genetics.